Low-rise Residential Complexes of PetersburgPetrograd-Leningrad of 1900-1941 Period Peculiarities of a New Residential Planned Unit Formation - Nikolaevna Rybalkina , Mariia (International Journal of Psychosocial Rehabilitation, 2019)
The historical background and characteristic features of the formation of low-rise residential complexes of Petersburg-Petrograd-Leningrad in 1900-1941 has been addressed in the state-of-the-art paper. The development of ideas for rational planning of the city and the self-sufficiency of residential units in its structure led to a rethinking of the historic quarter. In the evolution of the formation of residential planned units low-rise housing estates were the first experimental experience in the construction of a new residential planned unit in Leningrad. A number of advantages of this experience marked the beginning of the organization of construction of a new socially organized environment for the working class, which was a transition to a new stage in the development of Soviet housing architecture.